Angiosperms of Sendirakillai Sacred Grove (SSG), Cuddalore District, Tamil Nadu, India - G. Gnanasekaran; P. Nehru; D. Narasimhan (Check List, 2012)
We provide a checklist of Angiosperm alpha diversity of Sendirakillai Sacred Grove (SSG), a community conserved Tropical Dry Evergreen Forest (TDEF) fragment located on the Coromandel Coast of Cuddalore district (11°44’24” N, 79°47’24” E), Tamil Nadu, South India. Plant specimens were collected either with flowers or fruits and were identified and confirmed with available regional floras, revisions and monographs. In the present study, we have enumerated a total of 180 species and 2 varieties belonging to 151 genera distributed in 66 families from 29 orders according to Angiosperm Phylogeny Group III Classification. More than 30% of the total flora is represented by six families namely Fabaceae (14), Rubiaceae (12), Cyperaceae (10), Apocynaceae (8), Poaceae (8) and Euphorbiaceae (7). Three endemic species to India and three species that are confined to peninsular India and Sri Lanka are recorded from the sacred grove. Threats to the biodiversity of sacred grove are identified and conservation strategies are proposed.